A thermo-mechanical coupling load model for high-frequency piezoelectric ultrasonic transducer - Kuan Zhang; Guofu Gao; Wenbin Ma; Ruikang Li; Daohui Xiang; Junjin Ma (Ultrasonics Sonochemistry)
The ultrasonic micromachining systems significantly improve machining efficiency and quality, which are increasingly being applied in the manufacturing of microstructures and micro parts. However, the mechanical and thermal loads of the high-frequency piezoelectric ultrasonic transducer (HPUT) of ultrasonic micromachining systems have serious interference with the precise control of resonance frequency tracking, which further causes uncontrollable processing quality and precision. To improve the controllability of resonance frequency tracking, a thermo-mechanical coupling load model for HPUTs is proposed to establish the relationship between the resonance frequency and thermo-mechanical coupling load by introducing the force load constants and thermal load constants into the 6-terminal network electromechanical equivalent circuit. The experimental results show that the proposed thermo-mechanical coupling load model can accurately predict the trend of the resonance frequency when the thermo-mechanical coupling load is under the axial force range of 0–10 N and temperature range of 35–60°C.